2018
DOI: 10.18632/oncotarget.24680
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cachectic effect of Antrodia cinnamomea extract in lung tumor-bearing mice under chemotherapy

Abstract: Skeletal muscle atrophy, the most characteristic feature of cancer cachexia, often occurs in patients with cancer undergoing chemotherapy. Antrodia cinnamomea (AC) a widely used edible medical fungus, exhibits hepatoprotective, anti-inflammatory and anticancer activities. In this study, we investigated whether combined treatment with the ethonolic extract of AC ameliorates cachexia symptoms, especially muscle wasting, in lung tumor-bearing mice treated with chemotherapy. Our results revealed that gemcitabine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…Drug candidates focus on different biochemical targets that are involved in diverse molecular and physiological aspects that characterise the cachectic myopathy phenotype [ 40 ]. These candidates arise from a range of different therapeutic classes including activin receptor signalling inhibitors [ 59 , 60 , 100 , 103 , 165 ], appetite stimulants [ 77 , 80 , 82 , 166 , 167 , 168 , 169 , 170 ], nutritional supplements [ 171 , 172 , 173 , 174 , 175 , 176 ], and phytotherapies [ 112 , 113 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 ]. Activin receptor signalling inhibitors have shown strong pre-clinical efficacy to mitigate cancer and chemotherapy-induced cachexia through preserving skeletal muscle mass and function [ 186 ].…”
Section: Therapeutic Strategies To Mitigate Chemotherapy-induced Cachectic S Myopathy: An Updatementioning
confidence: 99%
“…Drug candidates focus on different biochemical targets that are involved in diverse molecular and physiological aspects that characterise the cachectic myopathy phenotype [ 40 ]. These candidates arise from a range of different therapeutic classes including activin receptor signalling inhibitors [ 59 , 60 , 100 , 103 , 165 ], appetite stimulants [ 77 , 80 , 82 , 166 , 167 , 168 , 169 , 170 ], nutritional supplements [ 171 , 172 , 173 , 174 , 175 , 176 ], and phytotherapies [ 112 , 113 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 ]. Activin receptor signalling inhibitors have shown strong pre-clinical efficacy to mitigate cancer and chemotherapy-induced cachexia through preserving skeletal muscle mass and function [ 186 ].…”
Section: Therapeutic Strategies To Mitigate Chemotherapy-induced Cachectic S Myopathy: An Updatementioning
confidence: 99%
“…In addition to pro-inflammatory cytokines, two particular members of the TGF-β family have been particularly explored in cancer cachexia: myostatin (MSTN) and Activin A. MSTN clearly represents one of the most potent negative regulator of muscle growth and is known to act through its receptor ActRIIB and the subsequent activation of the SMAD2/SMAD3 cascade ( Rodriguez et al, 2014 ). MSTN and/or its downstream targets have been found to be upregulated in many experiments on cancer cachexia ( Costelli et al, 2008 ; Bonetto et al, 2009 ; Zhou et al, 2010 ; Murphy et al, 2011 ; Aversa et al, 2012 ; Padrão et al, 2013 ; Chacon-Cabrera et al, 2014 ; Silva et al, 2015 ; Chen M. C. et al, 2016 ; Sun et al, 2016 ; Chen M. C. et al, 2018 ; Salazar-Degracia et al, 2018 ; Lee et al, 2019 ; Huot et al, 2020 ), as well as in studies exploring the effect of doxorubicin administration ( Kavazis et al, 2014 ; Liu et al, 2019 ). Acting through the same receptor than MSTN (ActRIIB), Activin A is also found to be increased in cancer cachexia ( Leto et al, 2006 ; Loumaye et al, 2015 ; Matsuyama et al, 2015 ; Chen J. L. et al, 2016 ; Chen M. C. et al, 2016 ; Barreto et al, 2017 ; Zhong et al, 2019 ; Bernardo et al, 2020 ) and an independent prognosis factor of survival in cancer patients ( Loumaye et al, 2017 ).…”
Section: Potential Other Cellular Mechanisms Of Muscle Deconditioning In Breast Cancer Patients: What Can We Learn From Other Cancers?mentioning
confidence: 99%
“…Tese protective characters come from the mycelium or fruiting bodies of AC through water or alcohol extraction [30,31] and unique triterpenoids isolated from AC [32]. In addition, earlier studies indicated that AC extract possesses potential anticachexia and antifatigue efects in chemotherapeutic drug-treated mice [33,34]. However, the molecular mechanism by which AC attenuates chemotherapeutic drug-induced muscle wasting remains unclear.…”
Section: Introductionmentioning
confidence: 99%